IMPLEMENTASI SISTEM INFORMASI PAYROLL PADA SEKOLAH GEMANURANI - Kresno Murti Prabowo; Zaenal Mutaqin Subekti (Jurnal Computech & Bisnis (e-Journal), 2021)
The development of the Gemanurani Integrated Islamic School information system encountered obstacles because it was carried out based on the personal needs of the developer at that time. So that the development carried out is not necessarily appropriate or has optimal benefit value in the future. Along the way, there have been many changes to forms, reports to system procedures. This shows that the development of the information system is not based on existing needs, so management is difficult to make decisions. Gemanurani Integrated Islamic School started the development of Information Systems for New Student Admissions (PSB), Finance, Administration (TU), Study Programs (PRODI), Students and Teachers without Human Resources Development (HRD). One of HRD's routine tasks is payroll where the implementation is still manually using MS. Excel, problems often arise when calculating teacher intervals, teachers across school programs and employee deductions. By prioritizing the development of a payroll information system that suits the needs, it is hoped that it will facilitate the HRD department in processing employee and teacher salaries. The goal is to make it easier for schools in time management and salary calculation security.  Keywords: payroll, information system, HRD.DOI : http://doi.org/10.5281/zenodo.4958348